Challenges faced by dental professionals during COVID-19- A cross sectional survey - Gupta, Swati; Hrishi, Thayyil Sivaraman; Gupta, Sumeet; Kumar, Sanjana; Javadi, Hamid; Gupta, Richa (Journal of Advances in Internal Medicine, 2020)
Background: At the time of pandemics like COVID-19, dental professionals being one of the frontline workers must face a lot of challenges in workplace bringing about a lot of anxiety and stress. The purpose of this survey was to assess the physiological well-being of the dental professionals, the majority of challenges faced by them, , how they are dealing with it and what changes in their opinion could be implemented to be prepared in the wake of any future adversity. Methodology: We conducted a cross sectional survey via an online questionnaire that was sent to dentists in 4 different countries- India, US, UK, and Iran. The questionnaire comprised of closed ended questions grouped in broad categories of demographics, physiological well-being of dentists, Changes in dental practice during COVID-19 and Changes to be implemented post Covid-19. Descriptive analysis was performed to summarize the data with SPSS-19 software. Results: A total of 312 dentists (181 Males and 131 Females) from four countries responded to the study. Most of them (56.4 %) were in the age group of 30 to 40 years, 27.9 % in 25- 30 years, and 7.1% above 50 years. 47.5% dentists reported suffering from stress and anxiety due to the shutting down of their private dental practices. 72.5% dentists reported that they are worried about the operational and financial challenges to run their practice during Covid-19. 60% of the dentists had concerns due to the shortage of personal protective equipment. Most of the dental professionals (73.9%) are of the opinion that management of medical emergencies should be included in the dental curriculum, so that dentists can volunteer their services at the time of crisis and also can be well-prepared to take care of their patients. Conclusion: During the COVID-19 pandemic, dentists like medical professionals must face a lot of ethical and moral dilemma along with dealing with the operational challenges. The present study draws our attention to the fact that despite having faced pandemics like SARS, health professions like dentistry still need a lot of preparedness and requires modifications to face any such challenges in future.